An overview of prospects of ethno-veterinary medicine in India - Krishana, Lalitha; Swarup, D; Patra, R C (The Indian Journal of Animal Sciences, 2005)
From the Vedic period till the end of 19th century, much of the veterinary practice in India was based on the experiences gathered through generations and improved through informal experimentation. This traditional system of medicine also referred to as ethno-veterinary medicine (EVM) is commonly defined as a system of folk beliefs, skills, techniques and practice relating to the healthcare of animals that is transmitted orally from generation to generation. However, a paradigm shift occurred in veterinary medicine with the introduction of modern system of veterinary during British period. Invention of antiseptics. sulfonamide and antibiotics brought revolutionary changes in veterinary medical practices and treatment of majorily of diseases was started with the newly invented synthetic drug molecule. Thus, the existing traditional knowledge was pushed to back seat till the advent of the concept of sustainable agriculture and livestock industry in the Indian agricultural scenario in late 1980s. Ethno-veterinary medicine, especially the traditional herbal remedies are now considered as a potential candidate for developing eco-friendly, safe and cost-effective drugs for animal uses. However, there is a need to address several challanges to promote the ethno-veterinary medicine as an effective, farmers' friendly and economically viable alternative method of animal treatment in the changing socio-economic and agro-geoclimatic conditions. There is a need to popularize natural drugs, and for cultivation of medicinal plants to ensure phytochemical consistency and quality. Enforcement of drug quality control and GMP, scientific validation of veterinary ITKs and improved availability of quality herbs at competitive price are some of the immediate problems that need to be addressed to enhance the prospects of ethno-veterinary medicine.